Law and the unconscious : a psychoanalytic perspective - Dailey, Anne C. (New Haven : Yale University Press, 2018)
This volume establishes the vital relevance of contemporary psychoanalysis to law. Our legal system is predicated on the idea that people act rationally and of their own free will. Yet the facts of mental life present a much messier picture.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 10, 2018).
Keywords: Law -- Psychological aspects; Subconsciousness; Forensic psychiatry; Psychoanalysis; Insanity (Law) -- United States; Law; Social, group or collective psychology; Jurisprudence & general issues; Private or civil law: general; Criminal law: procedure & offences; Family law